The Influence of Financial Literacy and Lifestyle on Financial Behavior among Students in Karang Taruna Cendrawasih Madurejo Yogyakarta - Fadhilah, Lia Nur (Yayasan Meira Visi Persada, 2024)
This research aims to determine the influence of financial behavior through financial literacy and the influence of lifestyle on Karang Taruna Cendrawasi students in Madurejo village. In this study, the population only consisted of students from Karang Taruna Cendrawasih Madurejo village and 100 students who were registered as members of Karang Taruna were used as samples taken using the random sampling method. The data used is primary data obtained from questionnaires distributed online. Classical hypothesis testing and multiple regression analysis using the SPSS V25.0 program were used for data analysis. Based on the results obtained, it can be concluded that: (1) the financial literacy variable has a significant positive influence on the financial behavior variable, (2) the lifestyle variable has a significant positive influence on the financial behavior variable. The variable influences the financial behavior of Karang Taruna Cendrawasih students in Madurejo village.